Reliability and validity of two tests of soccer skill - Ali, A.; Williams, C.; Hulse, M.; Strudwick, A.; Reddin, J.; Howarth, L.; Eldred, J.; Hirst, M.; McGregor, S. (Journal of Sports Sciences, 2007)
Twenty-four players from the 1st/2nd (elite) and 24 players from the 3rd/4th (non-elite) university football teams were recruited to evaluate the Loughborough Soccer Passing Test (LSPT) and Loughborough Soccer Shooting Test (LSST) as tools to assess soccer skill. The LSPT requires players to complete 16 passes as quickly as possible. The LSST requires players to pass, control, and shoot the ball to targets on a full-sized goal. Participants completed two main trials each separated by at least one day. During both trials, the participants were given practice efforts before recording the mean of the next two (LSPT) or 10 (LSST) attempts as the performance score. For the LSPT, the mean time taken, added penalty time, and overall performance time were less in the elite players (elite: 43.6 s, s = 3.8; non-elite: 52.5 s, s = 7.4; P = 0.0001). For the LSST, there was no difference in the mean points scored per shot between groups (elite: 1.34, s = 0.46; non-elite: 1.28, s = 0.53). However, the elite players had higher mean shot speed (elite: 80 km/h, s = 4.5; non-elite: 74 km/h, s = 4.2; P < 0.0001) and performed each shot sequence faster (elite: 7.87 s, s = 0.29; non-elite: 8.07 s, s = 0.35; P = 0.037) than the non-elite players. Performance on both tests was more repeatable in elite players. In conclusion, the LSPT and LSST are valid and reliable protocols to assess differences in soccer skill performance.